4+1 Complexes of zinc phthalocyanine with pyridine derivative ligands. (July 2015) - Przybył, Bartosz; Janczak, Jan
Abstract: Two complexes of zinc phthalocyanine monoaxially ligated by 3, 4-dimethylpyridine (1 ) and 4-ethylpyridine (2 ) were obtained in crystalline forms. Compound1 depending on the crystallisation condition crystallises in two crystalline modifications, i.e. monoclinic (P21 /c, 1m ) and orthorhombic (Pccn, 1o ), whereas compound2 crystallises only in one orthorhombic form (Pccn space system). Structures1o and2 are isotypic; an explanation of that behaviour was proposed. Each structure contains the zinc phthalocyanine and the ligand molecules in molar ratio 1:1, which was confirmed by X-ray single diffraction and thermogravimetric analysis. Ligation of the ZnPc by N-ring aromatic ligands with formation of complexes1 and2 does not change the colouring properties, but increases their solubility in the organic solvents comparing to the parent ZnPc pigment. Graphical abstract: Highlights: Axially ligated by pyridine derivatives of ZnPc complexes are obtained. Two polymorphic forms of ZnPc(3, 4-Dimepy) and one form of ZnPc(4-Etpy) are reported. UV–Vis spectra of ZnPcL dyes show that Pc π-system is not perturbed by the axial L. The ZnPcL dyes are about 3–4 times more soluble than the parent ZnPc pigment. 3D MESP maps are helpful for understand the interaction of ZnPc with pyridine derivatives.